The Dynamics of Divorce in Indonesian Muslim Families - Alex Kusmardani (PT Mattawang Mediatama Solution, 2024)
The development of divorce cases from year to year is very dynamic. Divorce occurs not only because of problems in the family but also because divorce is attached to the husband and wife, who are left behind due to death. Likewise, the judge's decision can affect the determination of divorce status. If the judge is unwilling or does not decide on the divorce, the marriage is not declared divorced. Therefore, divorce is defined as the breakup of the marital relationship with the judge's decision or the request of one of the parties. This article aims to find out the dynamics of divorce development in Indonesia. This research is library-based qualitative with a descriptive, critical, analytical approach and an interdisciplinary perspective, combining philosophical, psychological, sociological, juridical, and comparative methods. The results show that divorce and marriage exist in the world. In the jewish religion, divorce is permitted. In the catholic faith, divorce is prohibited, while in protestantism, it is allowed on the grounds of adultery. In islam, the majority of islamic jurists allow it and some islamic jurists ban divorce. Meanwhile, in indonesia, divorce is permitted by a court decision. Some regions with the most divorce cases are West Java, East Java, Central Java, North Sumatra, DKI Jakarta, Banten, South Sulawesi, And Riau. The factors that cause divorce are spouse conflicts, economy, leaving one party, domestic violence, drunkenness, gambling, neglect, one of them being imprisoned, adultery, polygamy, forced marriage, and disputes that lead to divorce. Efforts to prevent divorce include premarital education, family money management training, strengthening the basis of personality, family mediation, and rehabilitative assistance for divorced couples.